A Comparative Genomics Strategy for Targeted Discovery of Single-Nucleotide Polymorphisms and Conserved-Noncoding Sequences in Orphan Crops - Feltus, F.A.; Singh, H.P.; Lohithaswa, H.C.; Schulze, S.R.; Silva, T.D.; Paterson, A.H. (My University, 2006)
Completed genome sequences provide templates for the design of genome analysis tools in orphan species lacking sequence information. To demonstrate this principle, we designed 384 PCR primer pairs to conserved exonic regions flanking introns, using Sorghum/Pennisetum expressed sequence tag alignments to the Oryza genome. Conserved-intron scanning primers (CISPs) amplified single-copy loci at 37% to 80% success rates in taxa that sample much of the approximately 50-million years of Poaceae divergence. While the conserved nature of exons fostered cross-taxon amplification, the lesser evolutionary constraints on introns enhanced single-nucleotide polymorphism detection. For example, in eight rice (Oryza sativa) genotypes, polymorphism averaged 12.1 per kb in introns but only 3.6 per kb in exons. Curiously, among 124 CISPs evaluated across Oryza, Sorghum, Pennisetum, Cynodon, Eragrostis, Zea, Triticum, and Hordeum, 23 (18.5%) seemed to be subject to rigid intron size constraints that were independent of per-nucleotide DNA sequence variation. Furthermore, we identified 487 conserved-noncoding sequence motifs in 129 CISP loci. A large CISP set (6,062 primer pairs, amplifying introns from 1,676 genes) designed using an automated pipeline showed generally higher abundance in recombinogenic than in nonrecombinogenic regions of the rice genome, thus providing relatively even distribution along genetic maps. CISPs are an effective means to explore poorly characterized genomes for both DNA polymorphism and noncoding sequence conservation on a genomewide or candidate gene basis, and also provide anchor points for comparative genomics across a diverse range of species.